Heavy metal concentrations in selected medicinal plants and herbal product, and the effect of selenium on antioxidant activity of mas cotek (Ficus deltoidea jack) - Nayan, Dayang Safinah (2012)
Three studies were involved in this research. First study on medicinal plants and soils where the plants are grown was conducted with the aim of finding soil factors which influence heavy metals uptake by medicinal plants. This screening study were performed on heavy metals oncentrations in medicinal plants at 3 different sites (different soil types) and the soils on which the plants grow. Soil and plant samples were collected from FRIM External Research Station, Setiu, Terengganu (17 samples), Felda Agricultural Services Sdn Bhd, Jengka 25, Bandar Jerantut, Pahang (16 samples) and MARDI Jalan Kebun Station, Klang, Selangor (24 samples) with each sites having their own management practices. Each location has different soil types. History of fertilization for each sites also differed. Result of plants uptake, but it all depends on the prevailing soil conditions and soil types where the plants are grown. Continued from the first study, the second study was done to monitor whether common herbal teas in the market are safe to consumers in terms of heavy metals content. Thirty six samples of herbal teas were randomly purchased from the local market (15 Mas cotek herbal teas and 21 Misai kucing herbal teas). In general, heavy metals concentrations for both herbal teas are still under the maximum permissible levels except for Zn and Pb in Misai kucing herbal teas, and Zn and As in Mas cotek herbal teas. Other than that, the data also shows that Se is deficient in herbal teas especially Mas cotek herbal teas. Thus, it is suggested that both Mas cotek and Misai kucing herbal teas in the local market need to be monitored with regards to concentrations of heavy metals. While, in terms of its daily intake, average daily dietary intake (ADDI) values has not reached the threshold value. Therefore, there is no danger of toxic heavy metals originating from herbal teas to happen. Finally, for the third study, a glasshouse experiment was carried out to investigate the effect of selenium fertilization on the antioxidant activity of Mas cotek at the selenium rates of 0, 10, 20, 40 and 50 g Se/ha in limed (2 t/ha CaCO3) and unlimed soils treated with (100 kg P2O5/ha) and without P fertilizer. From this study, selenium content in Mas cotek was significantly increased with selenium application, and the highest selenium uptake were recorded when lime, P fertilizer and 50 g Se ha-1 were applied. In terms of the antioxidant activity, Se, in general, augments antioxidant activity in Mas cotek leaves, these activities being induced more effectively by higher Se concentration in the soils. In short, for maximum antioxidantthis study indicated that total heavy metals in plants were related with soil properties (pH, CEC, organic carbon and/or clay content), and its concentration in soils, but it all depends on location and plant parts involved. Therefore, it is concluded that soil properties and total heavy metals concentration in soils affect its availability for medicinal activity and Se content, the recommended fertilization rate is 50 g Se/ha when lime and P fertilizer were applied, although this rate will gradually affect plant growth.